A study of different heat effects on the processing of raw milk to drinking milk for commercialization: article / Siti Nur Hamraa Mohd Isa and Siti Noor Suzila Maqsood Ul- Haque - Mohd Isa, Siti Nur Hamraa; Maqsood Ul- Haque, Siti Noor Suzila (2017)
Heat treatment is applied on the raw milk in order to decrease the microbiological risk, reduce the effect of protein denaturation, lower the acidity in milk and longer the shelf life. The study is conducted in order to treat the raw milk with different heat treatment method, such as pasteurization and incontainer sterilisation, to investigate the effect of the heated raw milk with microbiology examination, protein denaturation, sensory evaluation and pH and to determine the best heat treatment method with or without preservative of raw milk to drinking milk to fulfil the customer demands. Low Temperature- Short Time (LTST) with incorporation with honey and cinnamon which act as preservatives in milk is the best heat treatment method due to prolong shelf life, less of microbial colony, does not affect the protein consumption and has optimum pH.